Stability consequences of fiscal policy rules - Jukka Railavo (Bank of Finland, 2004)
Using an optimisation-based model with endogenous labour supply and a proportional tax rate, we compare the stabilising properties of different fiscal policy rules.The economy is affected by shocks from both government spending and technology.The fiscal policy rule can be based on government liabilities or the government budget deficit.As both are given as measures of fiscal policy performance in the Stability and Growth Pact (SGP), we also use a fiscal policy rule based on the combination of the two.We compare the accounting definition of deficit with the economic definition which takes inflation into account.The fiscal policy rule based on debt, with monetary policy consistent with the Taylor principle, results in an unstable solution.However, a fiscal policy rule based on deficit produces stable solutions with a wide range of fiscal policy parameters.Moreover, we find that putting more weight on the deficit than the debt in the fiscal policy rule creates less cyclical responses to shocks.Finally we find out that the SGP definition of deficit performs as well as the real deficit based on the government budget constraint.
URN:NBN:fi:bof-20140807602
Keywords: E52; E31; E61; 330; inflation; fiscal and monetary policy; stabilisation